Effects of Ovariectomy and Estrogen Replacement Therapy on Laryngeal Tissue: A Histopathological Experimental Animal Study - ÖZBEYLİ, DİLEK (SAGE PUBLICATIONS LTD, 2011)
Objective. To determine the histopathological effect of estrogen deficiency and hormone replacement treatment on laryngeal tissue in ovariectomized rats. Study Design. Animal study. Setting. The study was conducted at the animal experiment laboratory of Marmara University School of Medicine, Istanbul, Turkey. Subjects and Methods. Six-month-old female Wistar albino rats were divided into the following 3 groups (n = 8 per group): sham-operated control, ovariectomized, and ovariectomized with estrogen replacement. Rats in the ovariectomized with estrogen replacement group received 17 beta-estradiol valerate (200 mu g/kg, subcutaneously) once a week. Animals were killed after 8 weeks of intervention. Results. Significant changes were observed in the ovariectomized group when edema in lamina propria, inflammation in squamous, respiratory epithelia and lamina propria, pseudostratification, and cilia loss were assessed. Except cilia loss, there were no significant differences in the assessments between the sham-operated control and ovariectomized with estrogen replacement groups. Conclusions. On the basis of histopathological evaluations, it was shown that estrogen replacement helped to improve laryngeal changes due to experimentally induced menopause.
Keywords: menopause; larynx; estrogen replacement; FEMALE VOICE; MENOPAUSE; WOMEN